Possible effect of OAS1 and TMPRSS6 but not DPP4 and ZNF335 polymorphisms on COVID-19 severity in the Czech population - Hubáček, Jaroslav A; Philipp, Tom; Adámková, Věra; Májek, Ondřej; Dlouhá, Dana; Dušek, Ladislav (Central European journal of public health, 2023)
OBJECTIVES: The acute respiratory syndrome, known as COVID-19, is characterised by high morbidity and increased mortality. Genetic factors may partially explain the differences in susceptibility to and severity of COVID-19. METHODS: We have analysed common functional polymorphisms within the OAS1 (rs4767027), TMPRSS6 (rs855791), DPP4 (rs3788979), and ZNF335 (rs3848719) genes in SARS-CoV-2 positive subjects (n = 521, different disease severity) and in population controls (n = 2,559 subjects, COVID-19 status unknown). RESULTS: Neither DPP4 nor ZNF335 were associated with disease susceptibility or severity in the Czech population in any of the models used for calculation. T allele carriers of the OAS1 polymorphism seem to be protective against symptomatic COVID-19 (p = 0.002 calculated for trend; asymptomatic, symptomatic, hospitalised). Similarly, within the TMPRSS6, minor TT homozygotes associated with lower plasma Fe concentrations were underrepresented in the overall patient group (p = 0.044; OR = 0.77, 95% CI: 0.59-0.99), and the difference was mainly driven by the severe COVID-19 subjects. In general, risky homozygotes of these two polymorphisms were less frequent than expected in the group of hospitalised COVID-19 survivors. CONCLUSIONS: Common variants within OAS1 (rs4767027) and TMPRSS6 (rs855791) play some role in COVID-19 pathology in the Czech Caucasian population. Whether the depletion of minor allele carriers of these two variants is associated with increased COVID-19 mortality, needs to be analysed in an external confirmatory study.
Keywords: Czech Republic; Humans; transkripční faktory; DPP4; OAS1; membránové proteiny; Serine Endopeptidases; lidé; polymorphism; severity; serinové endopeptidasy; Membrane Proteins; Polymorphism, Single Nucleotide; ZNF335; COVID-19; dipeptidylpeptidasa 4; DNA vazebné proteiny; TMPRSS6; Dipeptidyl Peptidase 4; 2',5'-Oligoadenylate Synthetase; 2',5'-oligoadenylátsynthetasa; Česká republika; Transcription Factors; SARS-CoV-2; DNA-Binding Proteins; jednonukleotidový polymorfismus